Reduced Birth Weight Caused by Sextuple Drug-Resistant Plasmodium falciparum Infection in Early Second Trimester. (3rd March 2021) - Hansson, Helle; Minja, Daniel T R; Moeller, Sofie L; Lusingu, John P A; Bygbjerg, Ib C; Yde, Anna-Mathilde; Jensen, Rasmus W; Nag, Sidsel; Msemo, Omari A; Theander, Thor G; Alifrangis, Michael; Schmiegelow, Christentze
Abstract: Mutations in the Plasmodium falciparum genes Pfdhfr and Pfdhps, particularly the sextuple mutant haplotype threatens the antimalarial effectiveness of sulfadoxine-pyrimethamine (SP) as intermittent preventive treatment during pregnancy (IPTp). To explore the impact of sextuple mutant haplotype infections on outcome measures after provision of IPTp with SP, we monitored birth outcomes in women followed up from before conception or from the first trimester until delivery. Women infected with sextuple haplotypes, in the early second trimester specifically, delivered newborns with a lower birth weight compared with women who did not have malaria during pregnancy (difference, −267 g; 95% confidence interval, −454 to −59; P = .01) and women infected with less SP-resistant haplotypes (−461 g; −877 to −44; P = .03). Thus, sextuple haplotype infections seem to affect the effectiveness of SP for IPTp and directly affect birth outcome by lowering birth weight. Close monitoring and targeted malaria control during early pregnancy is therefore crucial to improving birth outcomes. Abstract : In early stages of pregnancy (early second trimester), Plasmodium falciparum infections with the sextuple Pfdhfr / Pfdhps mutant haplotype affect the effectiveness of sulfadoxine-pyrimethamine as intermittent preventive treatment during pregnancy by lowering the birth weight of newborns.